Celebrating 120 Years of Butantan Institute Contributions for Toxinology - Ana M. Moura-da-Silva (Toxins, 2022)
A hundred and twenty years ago, the Butantan Institute was founded by the Brazilian physician and scientist Vital Brazil, combining, in the same institution, medical research, and the transfer of results to society in the form of health products [...]